Evaluation of settlement problems in dams by finite element method - Ozbay, Muhammed Ali; Mersin, Denizhan (My University, 2023)
Dams have a very important position in water resources engineering. Surface water is accumulated and a reservoir is created, and irrigation water and drinking water are met with this reservoir. However, some of the biggest problems encountered in dams are as follows; the water leaking under the dam body reduces the bearing capacity of the ground, and as a result, the piping phenomenon is observed and the dam body is faced with the possibility of collapse. However, one of the biggest problems encountered in dams is that the bearing capacity, void ratio and water content are not the same in every region of the ground where the body of the dam will consolidate. Due to such problems, geotechnical and hydraulic engineers in dams need to do a lot of research on the ground and find solutions to these problems. In this paper, some published work on the calculation of piping events due to settlements, deformations and seepage in dams will be interpreted and evaluated. Since the analytical method to find the piping events that may occur due to leakage is laborious and the margin of error is high, the results were obtained by using the finite element program in these two papers published on these problems. A numerical solution method is both fast and has a low margin of error with the finite element method. Modeling of these dams was carried out with the PLAXIS finite element program. The settlement values of the experimental instruments placed on the dam body floor were compared with the settlements obtained with PLAXIS software. It has been determined that the settlement values of the inclinometer and extensometer instruments placed under the dam for these three dams are incorrect. For such reasons, settlement analysis results were obtained with PLAXIS finite elements. This compilation study reveals the settlement of hydraulic structures to be resolved by the finite element method.
Bildiri - Yayımlanmış
Keywords: Hydraulics; Environment; Dams; Civil engineering; Finite element method